Self-Audit at Centre for Modern Languages Universiti Malaysia Pahang - Fathiah Izzati, Mohammad Fadzillah
Centre for Modern Languages (CML) – Recently, a self-audit involving General Subjects or was held in accordance with the directive issued by the Department of Higher Education. This audit process covered the work process/ mechanism the revision of course materials for teaching and learning purposes, as well as the development and vetting of items for the assessment and evaluation purposes.